2011
DOI: 10.1589/jpts.23.437
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the BODE Index and the GOLD Stage Classification of COPD Patients in the Evaluation of Physical Ability

Abstract: Abstract.[Purpose] The aim of this cross-sectional study was to test whether the body mass index (BMI), airway obstruction, dyspnea, and exercise capacity (BODE) index is superior to the global initiative for chronic obstructive lung disease (GOLD) classification for physical ability, and to ascertain the usefulness of the BODE index in chronic obstructive pulmonary disease (COPD) patients. [Methods] We studied 48 patients with stable COPD (mean [±SD] age: 76.2±7.0 years). We measured BMI, modified medical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
0
1
Order By: Relevance
“…22 MIP has been the traditional measure of inspiratory muscle strength in COPD. We found no significant differences in MIP among BODE quartiles, in contrast with findings from a study performed by Anami et al 23 However, we observed that MIP values tended to decrease gradually as BODE scores increased. Moreover, and again in contrast to the findings from Anami, our study showed a significant and inverse correlation between MIP and the BODE index.…”
Section: Discussioncontrasting
confidence: 99%
“…22 MIP has been the traditional measure of inspiratory muscle strength in COPD. We found no significant differences in MIP among BODE quartiles, in contrast with findings from a study performed by Anami et al 23 However, we observed that MIP values tended to decrease gradually as BODE scores increased. Moreover, and again in contrast to the findings from Anami, our study showed a significant and inverse correlation between MIP and the BODE index.…”
Section: Discussioncontrasting
confidence: 99%